Detectable depth of unexposed parathyroid glands using near-infrared autofluorescence imaging in thyroid surgery - Han, Young Seok; Kim, Yikeun; Lee, Hyoung Shin; Kim, Yeongjoon; Ahn, Yeh-Chan; Lee, Kang Dae (Frontiers in Endocrinology, 2023)
Background Near-infrared light can penetrate the fat or connective tissues overlying the parathyroid gland (PG), enabling early localization of the PG by near-infrared autofluorescence (NIRAF) imaging. However, the depth at which the PG can be detected has not been reported. In this study, we investigated the detectable depth of unexposed PGs using NIRAF during thyroidectomy. Materials and methods Fifty-one unexposed PGs from 30 consecutive thyroidectomy patients, mapped by an experienced surgeon (K.D. Lee) with the use of NIRAF imaging, were included. For NIRAF detection of PGs, a lab-built camera imaging system was used. Detectable depths of the unexposed PGs were measured using a Vernier caliper. The NIRAF images were classified as faint or bright depending on whether a novice could successfully interpret the image as showing the PG. Data on variables that may affect detectable depth and NIRAF intensity were collected. Results Detectable depth ranged between 0.35 and 3.05 mm, with a mean of 1.23 ± 0.73 mm. The average NIRAF intensity of unexposed PGs was 3.13 au. After dissection of the overlying tissue, the intensity of the exposed PG increased to 4.88 au (p < 0.001). No difference in NIRAF intensity between fat-covered (3.27 ± 0.90 au) and connective tissue-covered PGs (3.00 ± 1.23 au) was observed (p = 0.369). PGs covered by fat tissue (depth: 1.77 ± 0.67 mm) were found at deeper locations than those covered by connective tissue (depth: 0.70 ± 0.21 mm) (p < 0.001). The brightness of images of the faint group (2.14 ± 0.48 au) was on average 1.24 au lower than that of the bright group (3.38 ± 1.04 au) (p = 0.001). A novice successfully localized 80.4% of the unexposed PGs. Other variables did not significantly affect detectable depth. Conclusion Unexposed PGs could be mapped using NIRAF imaging at a maximum depth of 3.05 mm and an average depth of 1.23 mm. A novice was able to localize the PGs before they were visible to the naked eye at a high rate. These results can be used as reference data for localization of unexposed PGs in thyroid surgery.